Run-Off Farming in Reducing Rural Poverty in the Cholistan Desert (Global Journal of Human-Social Science, 2013)
This study provides an overview of the potential impact of employing indigenous rainwater-harvesting technology in alleviating poverty in the Cholistan Desert of Pakistan. Ideal characteristics for run-off farming catchments result from the combination of landforms and soil properties. Many soils in the region exhibit low to very low infiltration and high levels of run-off. It has been demonstrated that there is a direct relationship between water availability and poverty reduction. This study outlines both the advantages and disadvantages of the indigenous rainwater-harvesting technology in reducing rural poverty and recommends its use with modern water harvesting techniques.
Keywords: Catchment; Cholistan; environment; Hakra River; precipitation; runoff